International Students’ Perceptions of Printed Form of Outdoor Advertising - Khodadad, Mina (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2019)
Advertising is one of the most important elements in the promotion of products and services. Whether in developed or developing countries, advertising is the first tool used when companies want to promote their brands. Print advertising, broadcast advertising, out-of-home advertising, and new media advertising are all alternatives used by a company to reach their audience. Outdoor, transit, and kiosk advertising are specific types of out-of-home media advertising in practice today. This research tries to analyze the impacts and aspects of out-of-home advertising in urban cities on the level of people’s perceptions using the case study of Famagusta, North Cyprus. Since Famagusta is a university city, students from different nationalities constitute a significant percentage of the city’s population. Salamis is one of the most important streets in Famagusta, which has changed drastically during the last decade. Since this street is a main access road for students attending the university, there are many shops and restaurants located on it. Outdoor advertising, therefore, is used by these companies to reach this population with their ads. Since companies are spending a lot of money for these advertisements, the main aim of this study is to measure the efficiency and effectiveness of these out-of-home advertising tactics on the international students’ perception levels. As the theoretical framework for this study, the communication theories of persuasion, perception, and visual attention were used. Quantitative methods and survey methodology were also used in this study. With the convenience sampling method, 350 international students from different age groups and educational levels were chosen. These respondents were carefully selected to meet the requirements for participation in this study. Keywords: international students, Famagusta, out-door advertising, perception

ÖZ:Reklam, bir ürünün veya hizmetin tanıtılmasında en önemli unsurlardan biri olmaktadır. Gelişmiş veya gelişmekte olan ülkelerde bile bütün şirketler ürünlerini ve hizmetlerini tanıtmak istedikleri zaman kullandıkları ilk tanıtım aracı reklam olmaktadır. Şirketler, kitlelere ulaşabilmek için basılı reklam, radyo-televizyon reklamcılğı, dış mekan reklamcılık veya yeni medya reklamcılığı gibi alternatifleri kullanabilmektedir. Açık hava, transit ve Kiosk reklam türleri dış mekan medya reklamları çesitlerindendir. Bu araştırma, dış mekan reklamlarının şehirlerdeki etkilerini ve reklamlar ile ilgili insanların algılarını ölçmeye çalışmaktadır. Araştırma, Kuzey Kıbrıs’ta bulunan Gazimağusa şehrinde bir pilot çalışma olarak yapılmıştır. Gazimağusa’nın bir üniversite şehri oluşundan dolayı öğrenci grubunun içerisinde yabancı uyruklu öğrenci sayısı önemli bir paya sahiptir. Salamis yolu Gazimağusa’nın en önemli bölgelerinden biridir ve son yıllarda çok değişim geçirmiştir. Bu yol, öğrencilerin güzergahlarında bulunduğundan dolayı, üzerinde bir çok kafe ve restoran bulunmaktadır ve bir çok şirket bu güzergahta dış mekan reklamlar kullanmaktadır. Bu şirketler dış mekan reklamlar için çok yüksek ücretler ödemektedir. Bu araştırma yabancı uyruklu öğrencilerin reklamlara yönelik algılarını ve etkilerini ölçmeye çalışmaktadır. Bu çalışmada kuramsal çerçeve olarak, iletişim kuramlarından ikna etme, algı ve görsel dikkat kuramı kullanılmıştır. Nicel olarak yapılan bu çalışmada anket tekniği kullanılmıştır. Uygun örnekleme yöntemiyle farklı yaş grubundaki ve farklı eğitim seviyesindeki 350 uluslararası öğrenci seçilmiştir. Katılımcılar bu çalışmaya katılmak için gerekli koşulları sağlayacak şekilde dikkatlice seçilmiştir. Anahtar Kelimeler: Uluslararası öğrenciler, Gazimağusa, Dış mekan reklamcılığı, Algı.
Master of Arts in Communication and Media Studies. Institute of Graduate Studies and Research. Thesis (M.A.) - Eastern Mediterranean University, Faculty of Communication And Media Studies, 2019. Supervisor: Assoc. Prof. Dr. Anıl Kemal Kaya.
Keywords: Outdoor Adevrtising; International students; Famagusta; out-door advertising; perception; Communication and Media Studies